A Study of the Costs and Benefits of Textualism: The Supreme Court's Bankruptcy Cases - Robert K. Rasmussen (Washington University Law Quarterly, 1993)
Part I of this Article sets forth the two dominant theories of statutory interpretation currently advocated-textualism and dynamic interpretation. Part II of this Article examines the various policies of bankruptcy law. After setting forth the competing theories of statutory interpretation and the competing theories of bankruptcy law, Part III of this Article examines the Supreme Court's bankruptcy cases over the last seven terms.
Keywords: Law -- Interpretation & construction; Bankruptcy; Textualism (Legal interpretation)